PENGAWASAN DPRD BERDASARKAN NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH (STUDI DI DPRD KABUPATEN OGAN KOMERING ULU) - Yunda Ghozy Fatu Alima; Marwin Marwin; Arif Fikri (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
Regional government is the implementation of governmental affairs by regional governments and Regional House of Representatives (DPRD) based on the principle of regional autonomy. In its implementation, the DPRD has a supervisory function over the implementation of regional regulations to ensure that regional policies are carried out in accordance with statutory provisions. This study aims to analyze the supervisory function of the DPRD of Ogan Komering Ulu Regency in implementing regional regulations based on Article 153 of Law Number 23 of 2014 from the perspective of siyasah tanfidziyyah. The research used a qualitative method with a descriptive-analytical approach. Data were collected through field observations, interviews, and documentation. Primary data were obtained from members of the DPRD of Ogan Komering Ulu Regency, while secondary data were derived from laws and regulations, books, journals, and other supporting documents. The sampling technique used was purposive sampling involving seven respondents. Data were analyzed qualitatively through data reduction, data presentation, and conclusion drawing. The results showed that the supervisory function of the DPRD has been implemented through working meetings, field visits, and evaluations of regional regulation implementation. However, the supervision has not been fully optimal due to obstacles in coordination, follow-up supervision, and evaluation processes. From the perspective of siyasah tanfidziyyah, the supervisory function of the DPRD reflects a form of responsibility in realizing just, trustworthy, and people-oriented governance.